Symbole wykorzystywane w propagandzie wojennej okresu I wojny światowej w świetle ikonografii kart pocztowych - Grzegorz Biszczanik (In Gremium. Studies in History, Culture and Politics, 2013)
Symbols used in the warmongering during the First World War in the light of postcards iconographyFrom the very beginning of the First World War, each command of armies fighting in the conflict believed that quick, effective postal service helps to maintain high morals at the battle-front and encourages both soldiers and their families to communicate.Among numerous papers devoted to postcards, only a few aimed at taking a deeper look at the development of the history of postcards during the First World War. During the military conflict in Europe, postcards were used as a mass medium of communication reaching the citizens of both metropolis and deep province. The publishers did not avoid any subject: postcards depict images of general staff meetings, the Emperor’s visit at the battle-front or soldiers in military casinos or latrines.Postcards from the First World War period depicted documentary photographies, reproductions of daily papers with spectacular news as well as images of places and events. One could also find there the portraits of war participants and victims, images of daily life in trenches at the battlefield, as well as nostalgic landscapes connected with the images of families. War, as time of international conflict, made it natural to depict various images of the enemy created in each country involved in the conflict. Publishers were ideologically called to incite to war activities against every nation being outside alliance at that time.The aim of postcards publishers during the First World war period was neither an objective account from the battlefields nor revealing the truth about the people involved in the war, nor even people’s reaction to the war oppression. The battlefields or fights depicted at the postcards are stereotypical and in fact had nothing in common with the war reality to be seen at the battle-front. Since the creation of a postcard which is about 1869, postcards had shown cheerful subjects: the publishers exposed sentimental, humorous or romantic motives or the images of towns and villages. Dramatic subjects had been avoided, as it had probably been assumed that greeting should have had a positive nature, and symbols depicted at postcards had been meant to evoke positive feelings.Nevertheless, postcards were an important tool to spread the enemy images of propaganda nature as well as patriotic messages supported with reinforcing power of symbols. A significant, if not the most vital reason to use postcards in propaganda was their applicability to shape ideological or socio-political attitudes. At the beginning of the 20th century, the postcard became an ideal medium of conveying symbols and messages devoted to propaganda, especially due to its advantages; low price, popularity among various social groups, and above all the speed of information flow even in long distances. The necessity of concise postcard message as well as the fact that the page with the view depicted various symbols, influenced the reinforcement of the propaganda messages.A postcard was intensively used during the First World War period as a medium to share views, ideas, symbols as well as to shape the behaviors of mass consumers, deliberately exposing at them dramatic symbols or motives. These, universally used in Europe during the First World War, as a medium of mass communication, were functioning in great numbers in constant circulation between the battle-front and the homeland. Among various motives depicted at postcards at that time, it was the enemy images that are of prime focus due to their symbolism of propaganda activity.